Sustainable investing in equilibrium - Pástor, Ľuboš; Stambaugh, Robert F.; Taylor, Lucian A. (Journal of Financial Economics, 2021)
We model investing that considers environmental, social, and governance (ESG) criteria. In equilibrium, green assets have low expected returns because investors enjoy holding them and because green assets hedge climate risk. Green assets nevertheless outperform when positive shocks hit the ESG factor, which captures shifts in customers’ tastes for green products and investors’ tastes for green holdings. The ESG factor and the market portfolio price assets in a two-factor model. The ESG investment industry is largest when investors’ ESG preferences differ most. Sustainable investing produces positive social impact by making firms greener and by shifting real investment toward green firms.